(3YScQjIs - (3TeS GdOjf eMeO Hf YHO Gdedc, GHf ebOe,J (B583 (3g` s
(3ChdgG (B:s
(3bQjH GdbGFe GdegOi SjXgQ hHGdBNHGQ ai GdCbWGQ jTgQ s
(3BNQgG (B:s
(3eY GdBfUGQ hGdUMH GdcQGe HCda UdG Ydjge hGdJMjI s
(3gi ai fYJ GdfHi hXghQ GdegOi GdefJXQ HGdYScQ GdYXjes
(3JHUQI GdYfhGf (B:s
(3fXe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B249s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B20 s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs